Морфологічні особливості монокарпічних пагонів видів роду Miscanthus Anderss. у зв’язку з інтродукцією в Лісостепу та Поліссі України - Scherbakova, T.O.; Rakhmetov, D.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The peculiarities of the morphological structure of plant shoots of Miscanthus sinensis Anderss. and M. sacchariflorus (Maxim) Benth. due to introduction in Forest-Steppe and Polissya of Ukraine have been found. Peculiarities of formation and tillering of shoots have been defined. Monocarpic shoots of M. sinensis and M. saschariflorus are nonrosetteous short- and longrhizome respectively. Type of forming shoots of both species is extravaginal. Embryonic shoot forming and development of its underground and above-ground parts occur within two years in conditions of Forest-Steppe and Polissya of Ukraine. Plants of M. sinensis and M. saschariflorus form a monocyclic generative and vegetative shoots. Graphs of some morphological parameters of shoot metameres have been constructed. They look like single-humped and tricrotic curves and they are specific for each species.